On the Necessity to Improve the MIL-883E Standard - Gorskyi, P.V.; Gorskyi, G.P. (Journal of Thermoelectricity, 2025)
The necessity to improve the MIL-883 standard in order to more accurately determine the reliability indicators of thermoelectric generators (TEGs) is substantiated. It is shown that the failure time distribution law recommended by this standard follows from the assumption of a constant rate of relative degradation of the parameters of the tested products. Recommendations are given for the use of the MIL-883E standard for testing thermoelectric generators (TEGs). It is shown that the use of a diffusion-nonmonotonic failure time distribution instead of a logarithmic normal one allows for a significant reduction in relative errors, determination of TEG reliability indicators and a logical transition to the function of the probability of failure-free operation of an individual thermoelement.